Respons Struktur Dan Tingkat Kerusakan Portal Baja Akibat Variasi Pembebanan Dinamik Dengan Analisis Riwayat Waktu Non Linier - Vomania, Vomania; Suryanita, Reni; Kurniawandy, Alex (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Currently, steel is widely used as a starting material in the high-rise building structure because it is more effective and efficient. Otherwise, steel has some drawbacks i.e. prone in collapsed due to dynamic loading. Therefore the aim of this research is to determine of response structure due to dynamic loading. The model is an Open Steel Frame building with a height of 35 m along 10 floors. The type of dynamic loads is harmonic sine and cosines, El Centro earthquake. The dynamic loadings are more precise when they were analyzed using the nonlinier time history method. The harmonic loads on the earthquake load structure are magnitude P0 1 kN, 5 kN and 10 kN load, meanwhile used the history of the El Centro earthquake. Dynamic loads that work suddenly, caused the structure undergoes deformations are not fixed and always have a change within a specified time. The results of the study showed that of these three type of loads, the maximum displacement is 143,885 cm, the maximum velocity is -519,599 cm/dt and the maximum acceleration is 3197,623 cm/dt2 load of the structure caused by sinus. Based on this study it can be concluded that the maximum displacement, velocity and acceleration of a maximum load harmonic sine and cosines is directly proportional to the variation of the value of P0 values getting bigger because then the greater the deformation structure anyway.Key words: dynamic loading, response structure, harmonic loading, time history